PENGARUH STRATEGI PROMOSI TERHADAP MINAT BELI PADA UMKM ROJO SOSIS - Agus Hermawan (SMART Management Journal, 2022)
This study aims to determine and analyze the effect of promotional strategies on consumer buying interest at UMKM Rojo Sosis in Bantar Gebang Cikiwul rw 006. The sampling technique is determined by random sampling by distributing 105 questionnaires to consumers who come and buy. The analytical method used is the statistical analysis method consisting of simple linear regression analysis, simultaneous significance testing (f test), partial significance testing (t-test), and testing the coefficient of determination (R2). The results of this study indicate that there is a positive and significant influence of the Promotion Strategy variable (X) on Buying Interest (Y) UMKM Rojo Sosis in Bantar Gebang Cikiwul RW 006.